Risk factors for and consequences of positive valve cultures in patients who undergo cardiac surgery while receiving antimicrobial treatment for infective endocarditis - Johansson, Gustav; Sunnerhagen, Torgny ; 0000-0002-9240-2378; Gilje, Patrik; Ragnarsson, Sigurdur; Rasmussen, Magnus ; 0000-0003-1588-5473 (Infectious Diseases, 2024)
Introduction Cardiac surgery is required in up to half of the patients with infective endocarditis (IE). Positive valve cultures have been associated with higher in-hospital mortality. The aims were to identify risk factors for positive valve cultures and its relation to outcome. Methods Patients subjected to heart valve cultures due to surgery for IE in Skåne University Hospital, Lund, between 2012 and 2021 were identified through microbiology records. Risk factors for positive valve cultures and information on mortality and relapse were retrieved through medical records. Univariable and multivariable logistic regressions were performed. Results A total of 345 episodes with IE in 337 patients subjected to cardiac surgery were included and valve cultures were positive in 78 (23%) episodes. In multivariable logistic regression, preoperative fever (adjusted odds ratio (AOR) 2.6, 95% confidence interval (CI) 1.2–5.6, p = 0.02), prosthetic heart valve (AOR 3.3, CI 1.4–7.9, p = 0.01), a single affected valve (AOR 4.8, CI 1.2–20, p = 0.03), blood culture findings of S. aureus, enterococci, or coagulase negative staphylococci compared to viridans streptococci (AOR 20–48, p < 0.001), and a shorter duration of antibiotic treatment (p < 0.001), were associated to positive valve culture. One-year mortality was 13% and a relapse was identified in 2.5% of episodes. No association between positive valve cultures and one-year mortality or relapse was identified. Conclusions Positive valve cultures were associated to short preoperative antibiotic treatment, IE caused by staphylococci, preoperative fever and prosthetic valve but not to relapse or mortality.